Serum mBDNF and ProBDNF Expression Levels as Diagnosis Clue for Early Stage Parkinson's Disease - Yi, Xu; Yang, Yujia; Zhao, Zhengfan; Xu, Manyu; Zhang, Yuan; Sheng, Yingying; Tian, Junying; Xu, Zhiqiang (Frontiers in Neurology, 2021)
Parkinson's disease (PD) is one of the most common chronic, progressive and neurodegenerative diseases characterized clinically by resting tremor, bradykinesia, rigidity and postural instability. As this disease is usually detected in the later stages thus cure is often delayed, ultimately leading to disability due to the lack of early diagnostic techniques. Therefore, it is of great importance to identify reliable biomarkers with high sensitivity and specificity for the early diagnosis of PD. In this study, we aimed to investigate whether serum expressions of brain-derived neurotrophic factor (BDNF) and proBDNF can serve as biomarkers for the diagnosis of PD at early stage. 156 patients with limb tremor and/or bradykinesia meeting the inclusion criteria were assigned to either ex-PD group (PD cases) or ex-NPD group (non-PD cases) and then re-assigned to either po-PD group (with PD) or po-NPD group (without PD) at 1-year followed-up based on the results of the re-diagnoses as performed in accordance with MDS Parkinson's diagnostic criteria. To improve early diagnostic accuracy, grouping (PD group and non-PD group) at initial visit and follow-up were performed differently and independently. Serum BDNF and proBDNF levels were measured by enzyme-linked immunosorbent assays. The results demonstrated that serum levels of BDNF and BDNF/proBDNF were significantly lower in the ex-PD group (19.73±7.31 ng/ml and 0.09±0.05) as compared with the ex-NPD group (23.47±8.21 ng/ml and 0.15±0.12) and in the po-PD group (19.24±7.20ng/ml and 0.09±0.05) as compared with the po-NPD group (25.05±7.67 ng/ml and 0.16±0.14). However, significantly higher serum level of proBDNF was noted in the ex-PD group (235.49±60.75ng/ml) compared with the ex-NPD group (191.75±66.12 ng/ml) and in the po-PD group (235.56±60.80 ng/ml) compared with po-NPD group (188.42±65.08 ng/ml). In conclusion, BDNF/proBDNF can be used as biomarkers for early stage Parkinson’s Disease, in addition, BDNF plus proBDNF has better diagnostic value than does BDNF alone in the diagnosis of PD.